Accuracy of basic school teachers knowledge in the english terms materials of game better education - Ihwan Firmansyah (English Teaching Journal : A Journal of English Literature, Language and Education, 2019)
Students of the Elementary School have core competencies and basic competencies that must be achieved according to the 2013 curriculum contained in Minister of Education and Culture Regulation number 24 of 2016 concerning Core Competencies and Basic Competencies of Learning in the 2013 Curriculum on Basic Education and Secondary Education. In PERMENDIKBUD number 24 (2018) it is stated that curriculum objectives include four competencies, namely (1) spiritual attitude competency, (2) social attitude, (3) knowledge, and (4) skills. The competency is achieved through extracurricular, curricular and / or extracurricular learning processes. The importance of the correct use of terms in learning materials in schools is one of the important things where in the academic world the use of standard language is a must. In sports and health physical education material which on several occasions uses the term in English, remembering that sports culture originates from a global culture that uses the English term needs to be mastered appropriately by physical and physical education teachers. The questionnaire is used as a data collection tool that uses descriptive quantitative analysis and research data will be obtained from a questionnaire filled out by elementary school PJOK teacher participants in Bangkalan who attended the basic motion material socialization event carried out by the STKIP PGRI Bangkalan sports education study program. Data analysis techniques used by researchers in looking at the percentage of respondents from the questionnaire distributed. Based on the results of the research and discussion above it can be concluded that the understanding of the knowledge of the accuracy of the use of English terminology in the material of large ball games physical and sport education and the results of the analysis have shown that the accuracy of elementary school teachers in using the terminology in English to teach sports the body in elementary school the results are quite good.